Estimation of liver fibrosis by noncommercial serum markers in comparison with transient elastography in patients with chronic hepatitis C virus infection receiving direct‐acting antiviral treatment. Issue 2 (8th November 2018) - Knop, Viola; Hofmann, Wolf P.; Buggisch, Peter; Klinker, Hartwig; Mauss, Stefan; Günther, Rainer; Hinrichsen, Holger; Hüppe, Dietrich; Pfeiffer‐Vornkahl, Heike; Simon, Karl‐Georg; Berg, Thomas; Manns, Michael P.; et al.
Summary: Treatment decisions are based on extent of fibrosis in patients with chronic hepatitis C (HCV) infection. Noninvasive diagnostic tools may help to avoid liver biopsy. We investigated the diagnostic accuracy of noncommercial serum scores in comparison with transient elastography (TE). Data analysis was undertaken based on 2458 patients enrolled in the German Hepatitis C Registry, in a prospective, observational study. Aspartate aminotransferase‐to‐platelet ratio index (APRI), FORNS index and FIB‐4 score were calculated and the diagnostic accuracy was compared to TE. As estimated by TE, 955 (38.9%) patients had absence of significant fibrosis (SF), 736 (29.9%) patients had SF, and 767 (31.2%) patients were shown to have cirrhosis. Patients with absence of SF had a sustained virological response (SVR) rate of 97.9%, whereas SVR was attained in 96.2% and 92.2% in those with SF and cirrhosis, respectively ( P  < 0.0001). The area under the receiver operator characteristic curve (AUROC), sensitivity and specificity in discriminating of SF were 0.789, 0.596 and 0.939 by APRI; 0.838, 0.852 and 0.748 by FORNS index; and 0.828, 0.658 and 0.946 by FIB‐4 score. AUROCs for the prediction of cirrhosis, sensitivity and specificity were 0.881, 0.851 and 0.854 by APRI; 0.846, 0.948 and 0.628 by FORNS index; and 0.907, 0.907 and 0.848 by FIB‐4 score. In conclusion, in the present multicentre real‐world cohort, SF and cirrhosis were predicted with high accuracy with noncommercial serum markers using TE as reference. Further prospective long‐term follow‐up is necessary to compare biomarkers with TE concerning liver‐related outcome and overall mortality.